Derivación de las ecuaciones de Schrodinger y Dirac de la ecuación de Hamlton-Jacobi - Amoroso Rodríguez, L. (2017)
The Schrödinger and Dirac equations of quantum mechanics are derived from the Hamilton-Jacobi equation. It was assumed that the action for a periodic process is such that can be represented as a complex periodic function.